Campaign Expenditures in the United States, 1991-1992: Freedom of Information Act (FOIA) Data ([Verlag nicht ermittelbar], 1995)
These data are made available by the Federal Election Commission (FEC) through the Freedom of Information Act (FOIA) and are taken directly from campaign finance reports filed by candidates, political committees, and others required to file under the federal election laws for the 1991-1992 election cycle. The Candidate Master Data file (Part 1) contains a record for each registered candidate for federal office. It includes the candidate's name, address, party affiliation, incumbent/challenger status, identification number of the principal campaign committee, office sought, and election year. The Committee Master Data file (Part 2) contains a record for each registered committee for federal office. Information provided includes the committee's identification number, name, address, treasurer's name, committee designation and type, party affiliation, report filing frequency, special interest group category and connected organization's name, and multicandidate committee status. The Itemized PAC Contribution File (Part 3) contains one record for each type of contributor for each reporting period. Information included in this file covers the type and year of the report, the time period covered by the report, total contributions, net contributions, total contribution refunds, net operating expenditures, cash on hand, debts and obligations owed by and to the committee, contributions from individuals, and loans made or guaranteed by the candidate. The Itemized Individual Candidate Contribution File (Part 4) contains one record for each individual contributor during the 1991-1992 reporting period. Information provided covers the transaction type, amount, and date as well as contributor name, address, and occupation.